The Structure of EU Expenditure after 2020 and Integration Challenges - Stabryła-Chudzio, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article presents the latest concepts of integration models with particular attention to financial issues, i.e. the possible directions for spending EU funds after 2020 in view of possible new common economics, social and defense strategies. The reflections are based on a scenario approach, where the most important element is determining how realistically fiscal federalism can be introduced in the European Union. It follows from this that the analysis would have a political aspect, meaning possible institutional changes.